Psychology in Bosnia and Herzegovina, Croatia and Serbia - Čorkalo Biruški, Dinka; Jerković Ivan; Zotović, Marija; Krnetić, Igor (2007)
The article presents beginning and development of the psychology in three successor states of Former Yugoslavia: Bosnia and Herzegovina, Croatia and Serbia. The common origins of the development of the discipline were stresses as well as similarities and differences in the development of the sub-disciplines and specific areas of psychology that have been advanced in each particular county. A comparison of educational systems was given and possibilities for regional collaboration discussed.
Projekt MZOS
ENG